2020
DOI: 10.1002/mp.14353
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation imaging as a high‐resolution, remote, versatile 2D detection system for MR‐linac quality assurance

Abstract: To demonstrate the potential benefits of remote camera-based scintillation imaging for routine quality assurance (QA) measurements for magnetic resonance guided radiotherapy (MRgRT) linear accelerators. Methods: A wall-mounted CMOS camera with a time-synchronized intensifier was used to image photons produced from a scintillation screen in response to dose deposition from a 6 MV FFF x-ray beam produced by a 0.35 T MR-linac. The oblique angle of the field of view was corrected using a projective transform from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“… 23 Daniel A. Alexander et al., demonstrated the potential value of scintillation imaging for MR‐linac QA compared with film and comparable sensitivity and linearity to the ion chamber in response to changes in machine output. 24 RLI has been recently applied also to preclinical small animal radiotherapy for dose distribution verification, showing a good agreement with Monte Carlo dose calculations and GC film measurements for small field of size up to 20× 20 mm 2 . 25 Besides radiation therapy by photons, the good sensitivity and sub‐mm spatial resolution of RLI system, makes it a useful tool for the quality control of scanning proton beams that allows for the detection of deviations of a few percent in relative dose from the expected dose distribution.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“… 23 Daniel A. Alexander et al., demonstrated the potential value of scintillation imaging for MR‐linac QA compared with film and comparable sensitivity and linearity to the ion chamber in response to changes in machine output. 24 RLI has been recently applied also to preclinical small animal radiotherapy for dose distribution verification, showing a good agreement with Monte Carlo dose calculations and GC film measurements for small field of size up to 20× 20 mm 2 . 25 Besides radiation therapy by photons, the good sensitivity and sub‐mm spatial resolution of RLI system, makes it a useful tool for the quality control of scanning proton beams that allows for the detection of deviations of a few percent in relative dose from the expected dose distribution.…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, using the compact hardware design and image processing algorithms, a practical, reliable, and comprehensive solution has been provided based on RLI for high dose rate brachytherapy 23 . Daniel A. Alexander et al., demonstrated the potential value of scintillation imaging for MR‐linac QA compared with film and comparable sensitivity and linearity to the ion chamber in response to changes in machine output 24 . RLI has been recently applied also to preclinical small animal radiotherapy for dose distribution verification, showing a good agreement with Monte Carlo dose calculations and GC film measurements for small field of size up to 20× 20 mm 2 25 .…”
Section: Introductionmentioning
confidence: 99%
“…has been adopted in this work to avoid the measurement error as much as possible 29 . Regarding beam profiles, it has been observed that the inline profile exhibits more blurring in this angle 22 . The profile measurements in y‐axis are more subject to skewed perspective angle of the camera, and the oblique viewing angle limits image resolution in the y‐direction.…”
Section: Discussionmentioning
confidence: 99%
“…The reference points are selected according to the four corners of solid water, as performed in previous studies. 22 Using the light field method of calibrating pixel size, a scalable factor of 0.68 mm/pixel is determined. 23…”
Section: Image Acquisition and Processingmentioning
confidence: 99%
“…8 However, Cherenkov emission has been demonstrated as a beneficial tool for QA measurements related to beam geometry, 9 as Cherenkov intensity is monotonically related to dose. Cherenkov and scintillation imaging have been demonstrated as useful methods for various QA procedures in both traditional image-guided radiotherapy and MRgRT, [10][11][12] and this is exploited in this context for highresolution 3D positional measurement of the radiation beam. In this study, we developed a custom Cherenkov imagingbased solution to measuring mechanical-imaging-radiation isocenter coincidence on the MRIdian system, entitled Visual Isocenter Position Enhanced Review (VIPER).…”
Section: Introductionmentioning
confidence: 99%